Medical Nutrition Therapy In Enterocutaneous Fistula: A Step-By-Step Approach - Maggie Nathania; Diyah Eka Andayani (Indonesian Nutrition Association, 2021)
Enterocutaneous fistula (ECF) management is a challenge that requires a multidisciplinary team approach in achieving optimal clinical output. Nutrition as a component of management plays a vital role in determining the prognosis, both as a predictor of morbidity and mortality. Malnutrition can also occurs as a preceeding situation or complication of ECF caused by the underlying disease, decreased food intake, increased protein requirements associated with systemic inflammation, and increased nutrient loss associated with the amount of fistula output. Thus, nutrition management can act as prevention, therapy, or both. Nutritional medical therapy in ECF cases aims to adequately estimate nutritional needs, maintain fluid and electrolyte balance, and stimulate spontaneous ECF closure whenever possible. To achieve optimal outcome, nutrition needs analysis must be done individually by considering the etiology, anatomical location of the fistula, and the amount of output. In the following article, we will discuss a comprehensive step-by-step nutrition treatment, both from the nutritional routes consideration, macronutrient and micronutrient requirements, specific nutrients, pharmacotherapy, and monitoring and evaluation that need to be done to achieve optimal clinical outcomes.Â